Quantifying wheat blast disease induced yield and production losses of wheat: A quasi-natural experiment - Mottaleb, Khondoker Abdul; Hodson, David P.; Krupnik, Timothy J.; Sonder, Kai (Cambridge University Press, 2023)
Applying the difference-in-difference (DID) estimation procedure, this study quantifies the wheat blast (Magnaporthe oryzae pathotype Triticum) induced losses in wheat yield, quantity of wheat sold, consumed, or stored, as well as wheat grain value in Bangladesh in 2016 following a disease outbreak that affected over 15,000 ha. Estimates show that the blast-induced yield loss was 540 kg ha−1 on average for households in blast-affected districts. Estimated total wheat production loss was approximately 8,205 tons worth USD 2.1 million in during the 2016 outbreak. Based on these insights, we discuss the need for long-term assured investment and concerted research efforts in controlling transboundary diseases such as wheat blast, including the importance of weather forecast driven early warning systems and the dissemination of blast-resistant varieties.